PERANCANGAN PERANGKAT PENDETEKSI PELANGGARAN KENDARAAN BERBASIS INTERNET OF THINGS MENGGUNAKAN SENSOR INFRARED DAN DFMINI MP3 PLAYER DI PERSIMPANGAN EMPAT JALAN GEDEBAGE BANDUNG - Laela Mulyati; Dhika (INFOKOM (Informatika & Komputer), 2020)
The development of science and technology affects aspects of human life because it facilitates various activities and jobs. One technology that has a big role in changing human life is transportation technology, in this case land transportation. There are many problems on the road, one of which is a violation of road markings, one of which is that the driver stops crossing the stop line at a red light. Seeing the number of violations, we need a tool that can warn offenders. This tool works by detecting via infrared if it is blocked by a driver who crosses the stop limit, triggers the loudspeaker to sound and in parallel Arduino will send a notification to the telegram application.